Balloon angioplasty of arteries of the upper extremities in patients with extracranial giant-cell arteritis. Issue 9 (7th February 2006) - Both, M; Aries, P M; Müller-Hülsbeck, S; Jahnke, T; Schäfer, P J; Gross, W L; Heller, M; Reuter, M
Abstract : Objectives: To evaluate the outcome of balloon angioplasty in the arteries of the upper extremities in patients with giant-cell arteritis (GCA) and stenosing extracranial involvement. Methods: Percutaneous transluminal angioplasty (PTA) for symptomatic upper limb artery stenoses (n = 29) and occlusions (n = 1) resistant to medical treatment was carried out in 10 patients (all women, mean age 65 years) with GCA. Vascular lesions were located in the subclavian (n = 4), axillary (n = 10) and brachial (n = 16) arteries. Interventional treatment was accompanied by immunosuppressive drugs in all patients. Follow-up included clinical and serological examination, magnetic resonance angiography and colour duplex ultrasound. Results: Initial technical success of angioplasty was achieved in the case of all vascular lesions. In five patients, marked recurrent stenoses (vascular territories; n = 10/30) were found during follow-up (mean 24 months). The cumulative primary patency rate was 65.2%. All recurrent lesions developed in the territories of the initial long-segment stenoses. Repeated PTA (vascular territories, n = 8; patients, n = 5) provided a cumulative secondary patency rate of 82.6% and a cumulative tertiary patency rate of 89.7%. Conclusions: Despite a tendency to restenoses, balloon angioplasty of the upper-extremity artery, in combination with immunosuppressive treatment, is an efficient method for the treatment of extracranial GCA.